REINTERPRETING THE DOMESTICATION OF WOMEN IN MARRIAGE: Through Qira’ah Mubadalah - Via Nurjannah; Erha Saufan Hadana; Fitriliana; Fanny Tasyfia Mahdy (Universitas Islam Negeri Ar-Raniry, 2026)
The domestication of women in marriage represents a long-standing issue in fiqh al-munakahat that perpetuates unequal gender relations within Muslim households. Traditional understandings, which confine women to domestic roles, often arise from literal and patriarchal interpretations of Qur’anic verses and Prophetic traditions, particularly regarding qiwamah and the wife’s obedience. The shifting social realities of the modern world demand a more contextual and egalitarian reading of these sources. Qira’ah Mubadalah, introduced by Faqihuddin Abdul Kodir, offers a transformative framework that emphasizes mutuality, justice, and equality in marital relationships. This study seeks to examine the manifestations of women’s domestication within classical fiqh discourse, and the extent to which Qira’ah Mubadalah reconstructs the concept of marital relations toward equality and fairness. Employing a qualitative normative-philosophical approach, the research analyzes classical and contemporary Islamic legal texts through content analysis. The findings reveal that women’s domestication in traditional fiqh stems more from socio-cultural patriarchy than from intrinsic Islamic principles. The Mubadalah interpretation reframes marriage as a reciprocal partnership (mu‘āsyarah bi al-ma‘rūf), emphasizing cooperation and shared responsibility rather than subordination. Qira’ah Mubadalah emerges as a progressive hermeneutical model capable of deconstructing patriarchal readings of marriage and reconstructing Islamic family law in line with principles of gender justice.